ASSOCIATION BETWEEN PERCEIVED OCCUPATIONAL SAFETY AND HEALTH IMPLEMENTATION AND PERCEIVED ACADEMIC FUNCTIONING AMONG INDUSTRIAL ENGINEERING STUDENTS: A CROSS-SECTIONAL STUDY - Sudjono, Hary; Novareza, Oyong; Sholihah, Qomariyatus; Lukodono, Rio Prasetyo (JEMIS (Journal of Engineering & Management in Industrial System), 2026)
University learning environments include classrooms, laboratories, workshops, and field-based activities, making occupational safety and health (OSH) an important component of educational quality. This study examined the association between perceived OSH implementation and perceived academic functioning among industrial engineering students. A cross-sectional survey was conducted with 75 students from the 2023, 2024, and 2025 cohorts at Universitas Brawijaya, Indonesia. Before the main survey, a preliminary instrument test was conducted with 50 different respondents, with no overlap between the preliminary and main samples. The questionnaire assessed environmental safety and health, personal protective equipment availability, OSH supervision, OSH training, student safety awareness, emergency preparedness, and perceived academic functioning related to concentration, comfort, productivity, safety, and academic improvement. Internal consistency analysis, descriptive statistics, Pearson correlation, and ordinary least squares regression with heteroskedasticity-robust standard errors were applied. The instruments demonstrated high internal consistency across the assessed constructs. Perceived OSH implementation showed a strong positive association with perceived academic functioning, indicating that students who perceived better OSH implementation also tended to report better academic functioning. However, the strength of this relationship should be interpreted cautiously because both constructs were measured from the same respondents at the same time using the same response format, and some conceptual overlap exists between the measures. Discriminant validity between the composites was not established. Therefore, the findings support a strong association between broad perceptual constructs rather than a causal or clearly construct-distinct effect.